Selfie-Takers Prefer Left Cheeks: Converging Evidence from the (Extended) selfiecity Database - Manovich, Lev; Ferrari, Vera; Bruno, Nicola (Frontiers in Psychology, 2017)
According to previous reports, selfie takers in widely different cultural contexts prefer poses showing the left cheek more than the right cheek. This posing bias may be interpreted as evidence for a right-hemispheric specialization for the expression of facial emotions. However, earlier studies analyzed selfie poses as categorized by human raters, which raises methodological issues in relation to the distinction between frontal and three-quarter poses. Here we provide converging evidence by analyzing the (extended) selfiecity database which includes automatic assessements of head rotation and of emotional expression. We confirm a culture- and sex-independent left-cheek bias and report stronger expression of negative emotions in selfies showing the left cheek. These results are generally consistent with a psychobiological account of a left cheek bias in self-portraits but reveal possible unexpected facts concerning the relation between side bias and lateralization of emotional expression.